Crossing Doctrines: Conflating Standing and the Merits Under the Establishment Clause - Ashutosh Bhagwat (Washington University Law Review, 2020)
In American Legion v. American Humanist Ass’n, the Supreme Court upheld the constitutionality of a thirty-two-foot tall Latin cross honoring soldiers killed during World War I against an Establishment Clause challenge. In a concurring opinion, Justice Gorsuch argued that the case should have been dismissed for lack of standing. He claimed that lower court decisions upholding standing for “offended observers” to challenge government religious displays are inconsistent with standing law, and were driven by the Supreme Court’s holding in Lemon v. Kurtzman that government endorsement of religion violated the Establishment Clause. Since, Gorsuch concluded, a majority of the Court explicitly disowned the Lemon test in American Legion, it was now time to abandon offended observer standing as well. In this Essay, I argue that Justice Gorsuch is correct, but for the wrong reasons. Justice Gorsuch’s assertion that offended observer standing arose from the Lemon endorsement test is not supported by history. He is, however, correct that such standing is recognized only in the Establishment Clause context. The question then arises, is there something unique about substantive law in this area which justifies special standing rules. And that in turn raises the very complex question of how the “injury in fact” requirement of standing doctrine interacts with substantive law. My conclusion is that substantive law and injury are related because Congress possesses the power to create new injuries that would not have supported common law claims, and that it regularly exercises that power in the administrative context. On the other hand, the Constitution, acting on its own, should not be read to create new forms of injury. This means that the cases recognizing standing to challenge religious display are incorrect, because they rely on the Establishment Clause alone to create injury where none would have been recognized under the common law. The paper concludes by exploring the implications of this conclusion for the Establishment Clause, and for other areas of law. It ends with the important insight that if standing should not have been recognized in religious display cases, then the Supreme Court was also wrong to recognize standing in its leading cases considering Equal Protection challenges to affirmative action programs.
Keywords: Establishment clause; Lemon v. Kurtzman 403 U.S. 602 (1971); American Legion v. American Humanist Association 139 S. Ct. 2067 (2019); Standing; Offended observers; Religious displays; First amendment